International terrorism: concept and forms - Al Hussien, Hala Ghassan (Journal of Economic, Administrative and Legal Sciences, 2022)
The main aim of this research is to gettrue informations, in response to recent developments in the field of terrorism studies and The role of Islamic Laws in rejecting terrorism and its relation to international law. This paper with its data has reached a general framework for terrorism summarized by a well-known principle: the end justifies the means. If the purpose contains an assault on humanity's dignity, freedom, money, blood, and thought. International terrorism is one of the modern concepts that is linked to general international law, considering that terrorism has become transcontinental and no longer confined to a specific society, until it has an effect on foreign relations between countries. The scientific definition and control of this concept faced many problems. Due to the absence of an equitable scientific reference.
Keywords: terrorism; extremism; international terrorism; state terrorism